RISK OF CONCENTRATION WITHIN THE FRAMEWORK OF THE INTERNAL CAPITAL ADEQUACY ASSESSMENT PROCESS IN A BANK: METHODOLOGICAL AND APPLIED METHODS - Vovchak, Olha; Dmytrenko, Iryna (Socio-economic relations in the digital society, 2020)
The purpose of the paper is to develop methodological and applied aspects of taking into account the risk of concentration of banks’ activities within the concept of internal procedure for assessing the capital adequacy of the bank. The paper summarizes the differences in assessing the bank’s capital adequacy in terms of the concepts of regulatory and economic capital by highlighting the following criteria: target priority; types of risks considered; taking into account the relationship between different types of risks; disadvantages and advantages. As part of the development of methodological principles for assessing economic capital for unexpected risks, the following is specified: 1) a list of factors that should be considered when determining default on a particular debt instrument; 2) applied features of taking into account the effect of the concentration of the relevant types of debt instruments to ensure efficient capital allocation. It is substantiated that the risk of concentration on debt instruments is such that, first of all, it affects the amount of credit risk and does not affect market and operational risks. It is proved that the methodology of considering the risk of concentration should be reflected in the peculiarities of the distribution of economic capital in terms of individual business lines. The technology of considering the risk of concentration and assessing its impact on the planning of the bank’s profits, including through the use of the RAROC tool. The latter allows calculating the rate of return on capital, which will reflect the risk appetite of the bank and further determine priorities in the development of certain business lines to ensure consistency of profitability, volume and range of risks and the amount of capital to cover probable losses. In general, the most effective models of credit risk assessment are those based on default theory, the effectiveness of which significantly depends on the quality of default statistics on different types of debtors on different debt instruments. The assessment of credit risk parameters (PD and LGD) should be based on historical experience and empirical research and should not be based primarily on professional judgment.